Cross sectional analysis of vaginal Lactobacillus in asymptomatic women of reproductive age in Mumbai, India - Pramanick, Rinku; Parab, Shraddha; Mayadeo, Niranjan; Warke, Himangi; Aranha, Clara (The Journal of Infection in Developing Countries, 2018)
Introduction: Lactobacillus dominated vaginal microenvironment is associated with lower risk of genital infections. Numerous studies have reported geographic and ethnic variations in vaginal microbiome structure between healthy individuals from different race and ethnicity. India has a great diversity, so it is intriguing to find out if such divergences exist in vaginal lactobacilli. The present study aimed to investigate predominant Lactobacillus species in vaginas of healthy Indian women and screen isolates for lactic acid and H2O2 production. Methodology: 203 premenopausal women asymptomatic for any vaginal complaints were recruited. The lactobacilli isolates on MRS agar were identified by Multiplex-PCR and 16sRNA gene sequencing. RAPD was used to differentiate strains of same species. H2O2 and lactic acid was evaluated on TMB-HRP MRS agar and BCP-MRS agar respectively. Results: Lactobacilli were recovered from 107/109 (98.2%) women with normal microflora. L. iners 64.7% (68), L. crispatus 26.7% (28), L. reuteri 21.9% (23), L. jensenii 16.2% (17) and L. gasseri 15.2% (16) were the most frequently occurring vaginal lactobacilli in normal women. The vaginal microflora was dominated by either by a single (80%, n = 84) or a combination (20%, n = 21) of Lactobacillus species. Though most frequently identified, L. iners, coexisted only with other Lactobacillus species. All isolates were acid producers but H2O2 was produced by 94.2% isolates. Conclusions: Our study reports prevalent vaginal lactobacilli which could be explored as probiotics. Presence of heterogeneous Lactobacillus population highlights the cumulative effects of different lactobacilli maintaining vaginal health. Contrasting observations about L. iners reiterates its puzzling role in vaginal immunity, advocating further research.